The effects of caffeine on athletic agility - Lorino, A. J.; Lloyd, L. K.; Crixell, S. H.; Walker, J. L. (The Journal of Strength and Conditioning Research, 2006)
Caffeine has been shown to improve sprint time, anaerobic power, and reaction time, all integral aspects of agility. The purpose of this study was to determine whether an acute caffeine dose would enhance agility and anaerobic power. Sixteen subjects participated in a randomized, double-blind experiment and performed the proagility run and the 30-second Wingate test 60 minutes after ingestion of caffeine (6 mg/kg) or placebo. No significant change was observed in the proagility run after caffeine ingestion compared with placebo. Also, no significant change was observed in peak power, mean power, or percent power decrease. Agility is an integral component of athletic skill and any reasonable method for enhancing agility would benefit active individuals. However, results from this study indicate that a 6 mg[middle dot]kg-1 dose of caffeine does not impact agility as measured by the proagility run test or power output as measured by the 30-second Wingate test in recreationally active young adult males who are not habituated to caffeine.